A scoping review of what is known of the physical health of adults with autism spectrum disorder. (March 2018) - Cashin, Andrew; Buckley, Thomas; Trollor, Julian N; Lennox, Nicholas
Little research has been carried out on the physical health of people with autism spectrum disorder (ASD). From the studies conducted with both children and adults, few studies have moved beyond retrospective record analysis and survey and conducted health assessment. The majority of the studies are from the United States of America with a small number conducted in Europe. A scoping review was conducted to determine what is known of the physical health of adults with ASD and to identify research gaps. In addition to studies of adults, this review includes studies of children to determine possible health trajectories. From the findings, it can be stated with confidence that people with ASD have a high rate of comorbidity and increased risk for chronic disease.